Pengaruh Strategic Flexibility terhadap Sustainability Performance: Peran Mediasi Eco-Innovation dan Green Supply Chain Integration - Christin Susilowati; Muchammad Zuhri Ramadhani Abanan (Jurnal Ilmu Manajemen, 2026)
This study aims to analyze the effect of strategic flexibility on sustainability performance with the mediating roles of eco-innovation and green supply chain integration (GSCI) in manufacturing companies in East Java, Indonesia. The study is grounded in the Natural Resource-Based View (NRBV), which emphasizes the importance of environmentally based internal and external capabilities as sources of sustainable competitive advantage. This research employs a quantitative explanatory approach using purposive sampling of manufacturing firms registered in the PROPER program. Data were collected through a questionnaire survey and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that strategic flexibility has a significant effect on sustainability performance. Furthermore, strategic flexibility positively influences eco-innovation and GSCI. Both variables also have a positive and significant impact on sustainability performance. Mediation analysis confirms that eco-innovation and GSCI serve as partial mediators in the relationship between strategic flexibility and sustainability performance. These findings suggest that strategic flexibility not only directly enhances sustainability performance but also strengthens it through the development of environmentally friendly innovation and the integration of green practices throughout the supply chain. Theoretically, this study extends the NRBV by positioning strategic flexibility as a dynamic capability that bridges strategy and sustainability outcomes. Practically, the findings highlight the importance of integrating strategic flexibility with eco-innovation and green supply chain collaboration to enhance long-term competitiveness and sustainability performance in manufacturing firms.